UNDERSTANDING AS A PROBLEM OF EDUCATION - Nina I. Lobanova (Moscow Polytechnic University, 2016)
The article attempts to reflect on the attitudes that underlie the traditional and technological approaches to education. As a result of the research, the author concludes that both of these approaches are combined by an original explanatory setting, which arises spontaneously from our daily lives, and then, also unconsciously, becomes the basis of our worldview and our educational activities.The question of explanatory setting, underlying the entire education system, again raises the problem of interaction between student and teacher: how to combine this explanatory setting with the requirement (the desire) to understand (without this intention any of educational process is not successful, incomplete). The author focuses on such questions as: what is a phenomenon of understanding as an integral part of the educational process? What place it occupies in it? What is the correlation between the explanatory setting and understanding?